Dzieci w świecie problematyki finansowej – innowacyjny pakiet dla edukacji wczesnoszkolnej "Myślę, decyduję, działam – finanse dla najmłodszych" - Małgorzata Żytko (Problemy Wczesnej Edukacji)
The article is dedicated to the issue of developing skills and acquiring economic knowledge in early school-age children, in particular in the field of financial education. The concept of the innovative educational tool “I Think, Decide, Act-finances for the youngest” and the process of testing this didactic material for two and half years in grades 1–3 of primary schools in Poland were presented. The purpose of the abovementioned tool is to provide children with cognitive and social educational situations for independent and creative activity that requires solving economic, financial and social problems. The main research methods were a parallel group experiment and an interview with teach-ers. The results of studies comparing the level of knowledge and financial-mathematical skills of children in the pretest and posttest indicate a statistically significant increase in the level in experi-mental group in comparison with the control one. The teachers’ opinions on the application of the innovative tool in school practice show its didactic and educational value, with a particular emphasis on the quality of proposed mathematical open-ended problems related to the practical context.